Evaluation the courses of the Department of Educational Media College of Specific Education in light of the electronic press addressing the challenges of national security - Kafr El-Sheikh University - Egypt - Karam, Jihad Mustafa (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to identify issues related to the challenges of national security, which should be included in the courses of media and electronic journalism, and to analyze the decisions of media and electronic journalism in the Department of Educational Media in the light of these challenges. The study is based on an analysis of the qualitative content of the concepts that have been conducted on the subject of the study and the relationship between its components and the views expressed about them and the processes involved and the effects they produce. The problem of the Arab national security stems from the dangers, threats and challenges facing the Arab nation in all political, strategic, cultural, economic, religious and technological aspects. Qualitative education of the content of electronic journalism, which dealt with only (13.2%) of the courses of the study sample despite the technological advancement of the press National security, which amounted to (11.81%) only in spite of the instability experienced by the Arab world now.
Keywords: Concept; calendar; electronic press; national security